Non-ST elevation of acute myocardial infarction caused by probable acute stent thrombosis after drug eluting stent implantation: a case report - Bagus Andi Pramono, Budi Yuli Setianto (Universitas Gadjah Mada, 2012)
Nowadays, one of the modalities in performing reperfusion in coronary artery disease ispercutaneous coronary intervention. Before drug eluting stent era, the problem that occurs themost among interventional cardiologists is restenosis. After drug eluting stent era, restenosiscan be reduced significantly. Unfortunately, it further develops another problem, that is calledstent thrombosis. Mechanism of stent thrombosis is related to vascular response, thrombosis,coagulation, and clinical factors. Based on our experience, non-ST elevation acute myocardialinfarction is caused by probable acute stent thrombosis after drug eluting stent implantation.Therefore, the prevention and therapeutic approaches should be put first in our priority becauseit can provide a serious complication.